2002
DOI: 10.1046/j.1471-4159.2002.01216.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of extracellular glutathione by an astrocyte derived factor with properties comparable to extracellular superoxide dismutase

Abstract: Cultured rat and human astrocytes and rat neurones were shown to release reduced glutathione (GSH). In addition, GSH oxidation was retarded by the concomitant release of a factor from the cells. One possibility is that this factor is extracellular superoxide dismutase (SOD). In support of this, the factor was found to bind heparin, have a molecular mass estimated to be between 50 and 100 kDa, and CuZn-type SOD protein and cyanide sensitive enzyme activity were demonstrated in the cell-conditioned medium. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 39 publications
0
32
1
Order By: Relevance
“…Previously we have shown that primary rat astrocytes and a human astrocytoma cell line are able to retard the loss of GSH in minimal media, partially through the secretion of 'guardian' molecules [14]. One of these molecules was provisionally identified as extracellular SOD (EC-SOD or SOD3) [14] and this identification has now been confirmed by western blotting (Unpublished data).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Previously we have shown that primary rat astrocytes and a human astrocytoma cell line are able to retard the loss of GSH in minimal media, partially through the secretion of 'guardian' molecules [14]. One of these molecules was provisionally identified as extracellular SOD (EC-SOD or SOD3) [14] and this identification has now been confirmed by western blotting (Unpublished data).…”
Section: Introductionmentioning
confidence: 76%
“…One of these molecules was provisionally identified as extracellular SOD (EC-SOD or SOD3) [14] and this identification has now been confirmed by western blotting (Unpublished data). Astrocytes also secrete the cytosolic form of SOD1 (Unpublished data and [27]).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several groups have demonstrated that astrocytes export GSH to extracellular space; however, the transporter(s) involved in this process have not been identified yet [14][15][16][17][18]. Studies performed in cultured human retinal pigmented epithelial cells have demonstrated that GSH efflux could be mediated by two different mechanisms, one Na ?…”
Section: Introductionmentioning
confidence: 99%